1992
DOI: 10.1016/0953-5438(92)90019-c
|View full text |Cite
|
Sign up to set email alerts
|

How should fitts' law be applied to human-computer interaction?

Abstract: The paper challenges the notion that any Fitts' Law model can be applied generally to human-computer interaction, and proposes instead that applying Fitts' Law requires knowledge of the users' sequence of movements, direction of movement, and typical movement amplitudes as well as target sizes. Two experiments examined a text selection task with sequences of controlled movements (point-click and point-drag). For the point-click sequence, a Fitts' Law model that used the diagonal across the text object in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

1993
1993
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 13 publications
0
13
0
Order By: Relevance
“…However, RT and MT were affected by variables not ad- dressed by Fitts' Law, such as the angle between the target and start button, whether the target was on the right (ipsilateral) or left (contralateral), and the fidelity of the virtual hand. Some people have tried to generalize Fitts' Law (which was developed for 1D movement) to tasks involving two and even three dimensions (e.g., MacKenzie & Buxton, 1992;Sallnäs & Zhai, 2003); however, others have argued that additional characteristics of the task besides Fitts' original variables of target size and distance must be considered (Gillan, Holden, & Adam, 1992;Whisenand & Emurian, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…However, RT and MT were affected by variables not ad- dressed by Fitts' Law, such as the angle between the target and start button, whether the target was on the right (ipsilateral) or left (contralateral), and the fidelity of the virtual hand. Some people have tried to generalize Fitts' Law (which was developed for 1D movement) to tasks involving two and even three dimensions (e.g., MacKenzie & Buxton, 1992;Sallnäs & Zhai, 2003); however, others have argued that additional characteristics of the task besides Fitts' original variables of target size and distance must be considered (Gillan, Holden, & Adam, 1992;Whisenand & Emurian, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…There are conditions for which additional factors have to be accounted for, including eye movements (Chi and Lin, 1997) and ballistic arm movements (Hoffman, 1991). For the past 30 years, issues of computer interface design have driven much interest in Fitts’ law, helping to improve pointing time through improved screen layout and menu design (Gillan et al, 1992). More recently, it has been shown that Fitts’ law accurately describes the MTs of a one dimensional cursor in an electroencephalographically (EEG) driven brain–machine interface (BMI), both in normal subjects and in patients with amyotrophic lateral sclerosis and spinal muscular atrophy (Felton et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have found that dragging is slower and more error prone than pointing for the tasks of text selection [1], simple target acquisition [2] and hierarchical menu selection [3]. The input devices studied include the mouse [1,2,3], trackball and stylus [2].…”
Section: Introductionmentioning
confidence: 99%